Agriculture, nutrition, and health in global development: typology and metrics for integrated interventions and research. (26th February 2014) - Masters, William A.; Webb, Patrick; Griffiths, Jeffrey K.; Deckelbaum, Richard J.
Abstract : Despite rhetoric arguing that enhanced agriculture leads to improved nutrition and health, there is scant empirical evidence about potential synergies across sectors or about the mix of actions that best supports all three sectors. The geographic scale and socioeconomic nature of these interventions require integration of previously separate research methods. This paper proposes a typology of interventions and a metric of integration among them to help researchers build on each other's results, facilitating integration in methods to inform the design of multisector interventions. The typology recognizes the importance of regional effect modifiers that are not themselves subject to randomized assignment, and trade‐offs in how policies and programs are implemented, evaluated, and scaled. Using this typology could facilitate methodological pluralism, helping researchers in one field use knowledge generated elsewhere, each using the most appropriate method for their situation.